2001
DOI: 10.1002/1097-4644(20010401)81:1<102::aid-jcb1027>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of receptor for advanced glycation end-product (RAGE) and the JAK/STAT-signaling pathway in AGE-induced collagen production in NRK-49F cells

Abstract: Advanced glycation end-product (AGE) is important in the pathogenesis of diabetic nephropathy (DN), and captopril (an angiotensin converting enzyme inhibitor) is effective in treating this disorder. We have shown that the Janus kinase (JAK)/signal transducers and activators of transcription (STAT) cascade is responsible for AGE-induced mitogenesis in NRK-49F (normal rat kidney fibroblast) cells, but its role in renal fibrosis in DN remains unknown. Therefore, we have sought to determine whether JAK/STAT is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 204 publications
(140 citation statements)
references
References 48 publications
(66 reference statements)
5
129
0
2
Order By: Relevance
“…Type IV collagen is transcriptionally regulated by Smad1 under AGE stimulation in mesangial cells (47). Interestingly, our previous studies showed that RAGE and the JAK2-STAT1/ STAT3 pathway were involved in AGE-induced collagen production in NRK-49F cells (48). Furthermore, in this study, we found that p42/p44 MAPK activity was increased in AGEtreated cells, but this activity was unaffected by SNAP, SNP, and 8-pCPT-cGMP.…”
Section: Discussionmentioning
confidence: 42%
“…Type IV collagen is transcriptionally regulated by Smad1 under AGE stimulation in mesangial cells (47). Interestingly, our previous studies showed that RAGE and the JAK2-STAT1/ STAT3 pathway were involved in AGE-induced collagen production in NRK-49F cells (48). Furthermore, in this study, we found that p42/p44 MAPK activity was increased in AGEtreated cells, but this activity was unaffected by SNAP, SNP, and 8-pCPT-cGMP.…”
Section: Discussionmentioning
confidence: 42%
“…15 Control solutions always contained an appropriate amount (Ͻ1:1000 dilution for each) of vehicle: ethanol for aldosterone (Across Organics), DMSO for eplerenone (Pfizer Inc) and PD98059 (Merck KGaA), and distilled water for cycloheximide (Sigma Chemical Co). At subconfluence, the culture medium was replaced with serum-free medium for 24 to 30 hours to render the cells quiescent.…”
Section: Cell Culturementioning
confidence: 99%
“…RAGE expression increases whenever its ligands accumulate, and the interaction of RAGE with its ligand promotes the progression of several non-pulmonary diseases, including diabetic nephropathy, diabetic atherosclerosis, and neurodegenerative disorders (Brownlee et al, 1988;Schmidt et al, 2000Schmidt et al, , 2001Morcos et al, 2002). The binding of AGE, S100/calgranulins, and HMGB1 to RAGE on vascular endothelial cells, neuronal cells, smooth muscle cells, or inflammatory cells may activate a range of signaling pathways, including those involving ERK1/2 MAP kinase, p38 and SAPK/JNK MAP kinase, rho GTPase, PI-3 kinase, and JAK/STAT, as well as the downstream activation of NF-kB (Kislinger et al, 1999;Huang et al, 2001;Yeh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%